The triune drama of the resurrectionVia Levinas’ non-phenomenology - Morrison, G. (Sophia, 2003)
The article aims to develop the philosophy of Emmanuel Levinas as a valuable new perspective in understanding the triune drama of the Resurrection. Firstly, the juxtaposition of Levinas’ thought and Christian theology will be argued for, followed by a development of von Balthasar’s Trinitarian theology of the Resurrection. Especially, Levinas’ non-phenomenological notion of “otherness” will be used to offer an understanding of the Risen Christ’s “Otherness” as communicating the non-phenomenality of Holy Saturday to the disciples. As a result, we discover significant theological openings towards a vision of a Biblical God free from the constraints of ontological thinking and phenomenal experience.